Macrophages in radiation injury: a new therapeutic target. (3rd October 2018) - Meziani, Lydia; Deutsch, Eric; Mondini, Michele
ABSTRACT: Radiotherapy can induce toxicity in healthy tissues such as radiation-induced fibrosis (RIF), and macrophages are proposed as new profibrogenic cells. In this Point-of-View, we summarize the role of the immune response in ionizing radiation injury, and we focus on macrophages as a new therapeutic target in RIF.